The Effect of Question Answer and Relationships (QAR) Strategy Toward the Students’ Achievement in Reading Comprehension of Narrative Text - Wulan Sari, Ambar; Winona Emelia, Tengku (Jurnal Riset Ilmu Pendidikan, 2022)
The objective of the study was to find out the effect of Question Answer and Relationship (QAR) strategy toward the students’ achievement in reading comprehension of narrative text. The study applied the pre-experimental research and used cluster random sampling. The population of this study was 64 students of 2020/2021year in FKIP UMSU. They were from separated classes, each class consisted of 32 students so the sample was taken of 32 students. Since this study used pre-experimental, the sample only used one class where 32 students taught by using  Question Answer and Relationship (QAR) strategy as the sample of the data. The data was required by conducting essay test that consisted of 10 items. The result showed that t-observe was 1,84 higher than t-table 1,69; while the level of significance was 0,05. Based on the result of the analysis, the alternative hypothesis was accepted since it proved that Question Answer and Relationship (QAR) strategy significantly effects toward the students’ achievement in reading comprehension of narrative text. The percentage of influence on the students’ achievement in reading comprehension of narrative text by Question Answer and Relationship (QAR) strategy was about 98% and 2 % by the other factors